Chemical Characteristics of Beef Rendang from the Results of Coconut Milk Substitution with Fibercreme (Faculty of Animal Science Universitas Brawijaya, 2022)
Rendang is one of the original Indonesian dishes originating from Minangkabau, West Sumatra. Making rendang in general uses the main ingredients in the form of beef, coconut milk and various kinds of spices and seasonings. Coconut milk contains high saturated fat which has the potential to cause various degenerative diseases if consumed in excess. Coconut milk can be replaced with FiberCreme. FiberCreme is a non-dairy creamer that can replace coconut milk, the main component of which is dietary fiber. FiberCreme has a taste that is almost similar to coconut milk. Adding FiberCreme to food as a substitute for coconut milk will make it taste delicious and creamy. In fact, FiberCreme has a lower fat and calorie content. The purpose of this study was to determine the appropriate substitution treatment of coconut milk with FiberCreme for use in the manufacture of beef rendang. The research material used was gandik beef, coconut milk, FiberCreme, and rendang seasoning. This study used a completely randomized design consisting of P0 (100% coconut milk), P1 (75% coconut milk: 25% FiberCreme), P2 (50% coconut milk: 50% FiberCreme), P3 (25% coconut milk: 75% FiberCreme), P4 (100% FiberCreme) with 4 replications. Data analysis used ANOVA, followed by Duncan's Multiple Distance Test (DMRT) if the results showed significantly different or very significant effects. The values of moisture content, fat content, total calories, free fatty acids (FFA), and thiobarbituric acid (TBA) were used as variables to be analyzed. The substitution treatment of coconut milk with FiberCreme had no significant effect (P>0.05) on the moisture content of rendang, but it had a very significant effect (P<0.01) on fat content, total calories, free fatty acids (FFA), thiobarbituric acid (TBA). It can be concluded that the use of 100% FiberCreme gave the best results on the chemical characteristics of beef rendang.